ANALISIS DISTRIBUSI KERUSAKAN AKIBAT GEMPABUMI 27 MEI 2006 MELALUI PENDEKATAN KEGUNUNGAPIAN DI DAERAH WONOLELO DAN SEKITARNYA, KABUPATEN BANTUL, DAERAH ISTIMEWA YOGYAKARTA - Mulyaningsih, Sri; Husadani, Y T; Devi, L R; Irawan, S N (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2009)
Northern Wonolelo area till Berbah was the areas with the most damaged generated by an earthquake of 27 May 2006. On the other hand, volcanic rocks within circular features characterize the areas. Palaeovolcanism had intensively deformed their lithology, generated normal faults and shear joints, in radial pattern with the axis of the vent. The earthquake force reactivated the existing faults and shears. Area with past central eruptions easier to deformed than the others. Volcanic-stratigraphy analyses found three periods of explosively volcanisms intersecting with composite volcanisms, created three escarpments separating each others. There fore, there were three zones of the most damaged areas according to the distributions of central eruptions; i.e Wonolelo and it vicinities, Sudimoro (Segoroyoso) and its vicinities, and Watuadeg-Senthong and its vicinities. Further subsurface research is necessary to verify the central of old volcano that caused the damages.